Pengembangan Sistem Informasi Anggaran Desa Berbasis Cloud Computing untuk Meningkatkan Transparansi dan Akuntabilitas Pengelolaan Keuangan Desa Bumiharja - Aji, Sopian; Pratmanto, Dany; Rousyati, Rousyati; Melly Agustin; Tasya Desti Setiawan; Afida Nurul Yasmin; Andri Miftahul Akhyar (TEMATIK, 2023)
Development of a Cloud Computing-Based Village Budget Information System to Increase Transparency and Accountability in Bumiharja Village Financial Management. The Village Budget Information System has become a key component in efforts to increase efficiency and transparency in village financial management. This article discusses cloud computing-based developments, with a focus on Bumiharja Village. The use of cloud computing technology allows easier and safer access to village budget data, integrating all aspects of village financial management into one connected platform. With this system, stakeholders, including village residents, village government, and auditors, can monitor village budgets in real-time. This contributes to a high level of transparency because budget and expenditure data can be accessed publicly. In addition, this system helps increase accountability in village financial management. With proper and structured recording, errors and misuse of funds can be more easily detected. By providing accurate data, village governments can plan budgets more wisely, and village residents can have a better understanding of fund allocation. The development of a cloud-based computing system is a progressive step in creating an efficient, transparent, and accountable village financial management system. This means that this is a breakthrough that has the potential to have a positive impact on development and economic growth in Bumiharja Village.